A Pemilihan Ketua Osis Pada Smk Panjatek Bekasi Menggunakan Analytical Hierarcy Process (AHP): Pemilihan Ketua Osis Pada Smk Panjatek Bekasi Menggunakan Analytical Hierarcy Process (AHP) - Jaya Setia Negara Jaya; Melan Susanti (Himpunan Penggiat Teknologi Informasi Abrar Indonesia, 2023)
Panjatek Vocational School, Bekasi City, once a year always organizes the election of the OSIS chairman, in the election of the previous OSIS chairman chose a candidate the student council president first, the student council chairperson candidates are selected by the student body coach, the assessment of student council chair candidates consists of personality, organization, point of view and knowledge of the school. To assist in the assessment of prospective OSIS chairpersons, a decision support system (SPK) is needed that is able to provide alternative solutions to the election of prospective OSIS chairpersons. The method used in the decision support system for selecting candidates for OSIS chairman uses the Analytical Hierarchy Process (AHP) method for weighting criteria. Research aids in making applications use the PHP programming language, MySQL database and Dremwaver. Based on the test results obtained, namely Ihsan Riansyah-Dela Indriya, Fanaditya Dianda P-Lutfiah Aulia, Royyan Ahmad Fauzi - Florensia Maria. Fanaditya has the highest score with a score of 0.267, Second C3-Royan with a Score of 0.262 Third C1-Ikhsan with a Score of 0.11 with this result the elected OSIS chairman candidate can be recommended to advance in becoming the elected OSIS chairman in Panjatek Vocational School for the 2022-2023 period. Keywords: Selection of Candidates for Student Council Chairperson, DSS, AHP